ORO-DENTAL MANIFESTATIONS IN A CHILD WITH VISCERAL DWARFISM - Gabriela Păduraru; Anda Adam; Valeriu V. Lupu; Marin Burlea; Ancuța Ignat (Romanian Society of Oral Rehabilitation, 2016)
The oral cavity represents an important source of information about the health of a child. Oral lesions may manifest early, sometimes concomitant with a systemic disease, disappearing with general health improvement or later persisting in spite of the disease's remission. Also, these can present developmental abnormalities. Oral mucosal lesions are commonly found in patients with liver cirrhosis. We present the case of a 12 years old boy with liver transplant since he was 9 years old, for the biliary cirrhosis secondary to the biliary hypoplasia. The patient had also very low height and weight prior to liver transplant, advanced osteomalacia and many oro-dental manifestations. Severe growth delay and osteomalacia have multiple causes, due to the primary hepatic pathology and to the chronic malabsorption syndrome, also due to the post-transplant immunosuppressant medication. Orodental lesion type and severity depends on the age of the child. It is important to know when the systemic disorders started, their duration and type, as well as their impact. The oral cavity can be significantly affected by immunodeficiency, cholestasis, malnutrition and coagulopathy